Effects of wheelchair Tai Chi ball exercise on physical and mental health and functional abilities among elderly with physical disability. Issue 3 (4th May 2021) - Wang, Yong Tai; Goh, Chung-Hyun; Liao, Ting; Dong, Xuanliang Neil; Duke, Gloria; Alfred, Danita; Yang, Yi; Xu, Jingle; Yu, Shiqi
ABSTRACT: The purpose of this study was to examine the effect of a 12-week Wheelchair Tai Chi Ball (WTCB) intervention, a combination of mind-body exercise with strength training, on physical and mental health and functional abilities among elderly with disability. Twenty-six elderly persons participated in the study, nine WTCB group participants and ten control group participants completed the study. The WTCB group practised WTCB12 twice/week for one hour each time. The control group did their daily routine without WTCB intervention. The outcomes measures were: Pain Self-Efficacy Questionnaire (PSEQ), SF-36v2 for physical and mental health, heart rate, blood pressure, range of motion and muscle strength of the dominant arm at the shoulder, elbow and wrist joints. The Mixed Model ANOVA was employed to examine the differences between and within the two groups using pre-test and post-test scores. The results demonstrated the WTCB group had significant improvements on PSEQ, general physical health and had positive effects on maintaining muscle strength at the shoulder, elbow and wrist joints as compared to the control group. The WTCB12 exercise had positive effects on self-efficacy for pain management, general physical health, and maintain upper extremity muscle strength and is a feasible exercise for elderly with disability.